Impact of oil and gas price shocks on the non-performing loans of banks in an oil and gas-rich economy - Saif-Alyousfi, Abdulazeez Y.H.; Saha, Asish; Md Rus, Rohani (Emerald Publishing Limited, 2018)
Purpose:The purpose of this paper is to examine and compare the impact of oil and gas prices shocks on the non-performing loans (NPLs) of banks at the aggregate as well as at the level of commercial and Islamic banks in Qatar over the period 2000-2016.Design/methodology/approach: Using the West Texas Intermediate Database, BankScope Database, World Bank’s World Development Indicators Database, and International Monetary Fund Database, the authors use a one-step system generalized method of moments dynamic model to examine and compare the association between oil and gas prices shocks with NPLs in Qatari banks. The authors also test the hypotheses of direct and indirect impacts of oil price shocks and gas price shocks on bank NPLs.Findings:The results indicate that oil price shocks and gas price shocks do not have directly affect NPLs of Qatari banks at the aggregate level, while they have indirect effects that are channeled through the country-specific macroeconomic and institutional factors.The authors find that oil and gas prices shocks affect NPLs of Qatari Islamic banks directly through extended oil and gas-related cash flows, while their impact on the NPLs of Qatari commercial banks is indirect. In other words, Islamic banks in Qatar greatly benefits from increased cash flow caused by the rise in the oil and gas prices, which make their NPLs, much lower than that in commercial banks.Better capital cushion, better managerial efficiency, better risk management, and liquidity management systems should be used by the Islamic banks in Qatar to expand their customer base. The authors also find that positive fiscal stance of the government reduces the NPLs in both commercial and Islamic banks.Practical implications: The results of this study necessitate policy measures that can counter the effects of changes in oil and gas prices on the growth of bank NPLs.Originality/value: It is widely recognized that oil and gas prices and the level of production are of great importance to the economic development of oil and gas-exporting countries.So far, however, no econometric study has been reported in the literature which analyses and compares the impact of oil and gas prices shocks on the NPLs of commercial and Islamic banks and also at the aggregate level in any of the oil economies.Thus, this study provides the first empirical evidence on distinct direct and indirect channels through which oil and gas prices shocks may affect bank NPLs.